Pathogenic SLC25A26 variants impair SAH transport activity causing mitochondrial disease. Issue 12 (13th January 2022) - Schober, Florian A; Tang, Jia Xin; Sergeant, Kate; Moedas, Marco F; Zierz, Charlotte M; Moore, David; Smith, Conrad; Lewis, David; Guha, Nishan; Hopton, Sila; Falkous, Gavin; Lam, Amanda; et al.
Abstract: The SLC25A26 gene encodes a mitochondrial inner membrane carrier that transports S-adenosylmethionine (SAM) into the mitochondrial matrix in exchange for S-adenosylhomocysteine (SAH). SAM is the predominant methyl-group donor for most cellular methylation processes, of which SAH is produced as a by-product. Pathogenic, biallelic SLC25A26 variants are a recognized cause of mitochondrial disease in children, with a severe neonatal onset caused by decreased SAM transport activity. Here, we describe two, unrelated adult cases, one of whom presented with recurrent episodes of severe abdominal pain and metabolic decompensation with lactic acidosis. Both patients had exercise intolerance and mitochondrial myopathy associated with biallelic variants in SLC25A26, which led to marked respiratory chain deficiencies and mitochondrial histopathological abnormalities in skeletal muscle that are comparable to those previously described in early-onset cases. We demonstrate using both mouse and fruit fly models that impairment of SAH, rather than SAM, transport across the mitochondrial membrane is likely the cause of this milder, late-onset phenotype. Our findings associate a novel pathomechanism with a known disease-causing protein and highlight the quests of precision medicine in optimizing diagnosis, therapeutic intervention and prognosis.